(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2026)
Objective: To assess the safety and efficacy of topical wound treatment with mesenchymal stromal cells derived from bone marrow cultured and suspended in platelet lysate. Method: A prospective, interventional, controlled study was conducted with 42 C57BL/6 mice with induced excisional wounds. They were divided into four treatment groups: hydrogel (standard wound treatment), saline gel (control), platelet lysate gel, and platelet lysate gel containing mesenchymal stromal cells. Immunohistochemistry analyses were performed on day 7 (n=5) and day 13 (n=7), and safety on day 21 (n=30). Follow-up was conducted through clinical (adverse events, weight, pain, behavior, wound size reduction) and histological (healing, vascularization, collagenization) assessments. Results: Regarding safety, no adverse events or physiological changes related to the treatment were identified. The group treated with cells showed better results in wound healing through macro and microscopic assessments, followed by the platelet lysate gel group. Conclusion: The topical application of mesenchymal stromal cells was safe and showed favorable results.